1987
DOI: 10.1080/02772248709357212
|View full text |Cite
|
Sign up to set email alerts
|

Toxic organic substances in sewage sludges: A case study of Soil‐Plant transfer

Abstract: The use of sewage sludges in agriculture has resulted in increased organic pollution of soils.A study of these pollutant transfers has been started at our research centre. The following points were particularly studied:-The penetration of organic pollutants in the plant. Does it take place at root level or by air transport? -Do the soil characteristics influence the transfer? -How does the contribution of sewage sludges influence the intake of organic pollutants?To answer these questions, we carried out a tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Quantitative pathways analyses show that if sludge is applied to arable land, there is very little likelihood that persistent organic contaminants will enter the food chain via crop uptake ( ). A more important pathway is if sludge is applied to pasture land ( ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantitative pathways analyses show that if sludge is applied to arable land, there is very little likelihood that persistent organic contaminants will enter the food chain via crop uptake ( ). A more important pathway is if sludge is applied to pasture land ( ).…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of chemical remaining on the vegetation over time potentially supplies terrestrial food chains, such as the pasture grass f grazing livestock f human pathway. Hence, several studies have sought to provide understanding of the processes that influence plant concentrations, focusing on the airplant (1-6) and soil-plant (1,(7)(8)(9)(10) transfer routes of persistent, semivolatile, and bioaccumulative compounds. These have generally shown that air-plant transfer via dry gaseous, particulate, and wet deposition dominates the supply of semivolatile organic contaminants (SOCs) (such as PCBs, PCDD/Fs, and PAHs) to the above-ground portions of plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation